Gerenciamento da Infraestrutura de Comunicação baseado na Distribuição Gaussiana do Tempo de Contato entre Veículos e a Infraestrutura - Silva, Lucas; Souza, Fernanda Sumika H.; Guidoni, Daniel Ludovico; Sarubbi, João F. M.; Pitangui, Cristiano; Silva, Cristiano Maciel da (Anais do Workshop de Gerência e Operação de Redes e Serviços (WGRS), 2019)
Seeking novel solutions for urban mobility seems paramount for 21st century society. This work discusses the performance of vehicular networks relying on the Delta Network. Delta characterizes the connectivity of the vehicular network by the percentage of travel time in which the vehicles are connected to the infrastructure. This work presents a novel deployment strategy based on the Gaussian distribution of the percentage of the trip duration in which vehicles are covered by the infrastructure. Roadside units are distributed throughout the urban area through a heuristic based on weights assigned according to the trips that are covered by the new roadside unit. The most important gain of this approach is that the resulting coverage pattern favors most of the fleet experiencing similar connectivity, while vehicles with very low or very high connectivity become the exception. The results demonstrate that the heuristic reaches its goal, promoting the distribution of percentage times of contact of vehicles with the infrastructure according to the Gaussian distribution.